Biocompatibility assessment of modified Portland cement in comparison with MTA® : In vivo and in vitro studies - I Khalil; J Isaac; C Chaccar; J M Sautier; A Berdal; N Naaman; A Naaman (Wolters Kluwer Medknow Publications, 2012)
Aim: The aim of our study is to elaborate a new cement based on Portland cement (PC), Modified Portland Cement (MPC) with modified chemical and physical properties that allow easier clinical manipulation and faster setting time than MTA® and then to evaluate its cytotoxicity in vitro and its biocompatibility in vivo in comparison with MTA® . Materials and Methods: Elaboration of MPC: Portland cement powder slenderly grinded to homogenize the particles, mixed with a radiopaque element and a setting time accelerator. A comparative in vitro study (MTS test) of the toxic effect of MTA® and MPC with culture isolated from the calvaria of 18-day-old fetal Swiss OF1 mice are done. A comparative in vivo study of the biocompatibility of MTA® and MPC: Under general anaesthesia, three holes (2.5 mm) were made in both the left and right femurs of six White New Zealand rabbits. In the first hole MPC is placed, in the second MTA® and the third one is left empty (negative control group). Three weeks after implantation, two rabbits are sacrificed, then two other rabbits over six weeks and the last two after twelve weeks. The neck of the femur is trimmed and prepared for undecalcified histological studies. Mann-Whitney test was used to analyze the results. Results: The cell viability test according to the morphological observations suggested the biocompatibility of the two biomaterials tested. The in vivo test showed similar biocompatibility between MTA® and MPC. Bone healing and minimal inflammatory response adjacent to MTA® and MPC implants were observed at all experimental periods (3, 6 and 12 weeks), suggesting that both materials are well tolerated. Conclusion: This pilot comparative study of MTA® and MPC showed no or very limited toxic effects of both cements in vitro and similar biocompatibility in vivo. However, additional in vivo and clinical studies should be done on MPC before it can be introduced in our clinical practice.